Such stuff as dreams are made on: John Bowlby and the interpretation of dreams - van der Horst, Frank C. P.; van der Veer, Rene; Duschinsky, Robbie (My University, 2020)
In this paper, newly uncovered archival material from the Bowlby archives is presented on Bowlby's own dreams and dream interpretation. Although he was critical of orthodox psychoanalysis, Bowlby appears to have been seriously involved in Freudian dream interpretation in the 1930s and 1940s. Here, we present in annotated form his own interpretations of several of his dreams from that time and a series of lectures on dreams. In Attachment and Loss, classic dream interpretation is absent and Bowlby used the content of dreams as a reflection of the influence of real-life experiences on the representations of attachment relations, with a clear focus on grief, loss, and mourning. Bowlby's shift from psychoanalysis to a more behavioral approach and the introduction of the concept of "defensive exclusion" to supplant Freud's concept of "repression" may have led him to think about how grief and mourning may affect the content of our dreams.
Keywords: dream interpretation; psychoanalysis; attachment; defensive exclusion; grief and mourning